2009
DOI: 10.1534/genetics.109.104927
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Regulation of Metabolism Associated With the Increased Desiccation Resistance of the Cactophilic Drosophila mojavensis

Abstract: In Drosophila, adaptation to xeric environments presents many challenges, greatest among them the maintenance of water balance. Drosophila mojavensis, a cactophilic species from the deserts of North America, is one of the most desiccation resistant in the genus, surviving low humidity primarily by reducing its metabolic rate. Genetic control of reduced metabolic rate, however, has yet to be elucidated. We utilized the recently sequenced genome of D. mojavensis to create an oligonucleotide microarray to pursue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 78 publications
7
47
1
1
Order By: Relevance
“…In a recent study, we showed that heat shock protein 70 (Hsp70) and Hsp90 are essential in the mosquito's response to dehydration stress . Significant changes in metabolic genes have also been noted in response to dehydration resistance in Drosophila (Matzkin and Markow, 2009). In addition to changes in protein and gene levels, other molecules including trehalose and glycerol are likely to be generated to prevent protein interactions and reduce membrane changes as water levels within the mosquito fluctuate (Goyal et al, 2005;Watanabe, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, we showed that heat shock protein 70 (Hsp70) and Hsp90 are essential in the mosquito's response to dehydration stress . Significant changes in metabolic genes have also been noted in response to dehydration resistance in Drosophila (Matzkin and Markow, 2009). In addition to changes in protein and gene levels, other molecules including trehalose and glycerol are likely to be generated to prevent protein interactions and reduce membrane changes as water levels within the mosquito fluctuate (Goyal et al, 2005;Watanabe, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Given that, in nature, tropical species face conditions that are above the thermal threshold that elicits cold reproductive arrest, the sharing of the reduction in metabolic rate across species may be a relictual plastic response that was present in the common ancestor of the buzzatii complex, despite the likely tropical origin of these flies. Alternatively, the reduction in metabolic rate may have been shaped by other stressors, such as desiccation, common to all cactophilic flies (Gibbs et al, 2003;Matzkin and Markow, 2009). A prediction of the latter interpretation is that similar responses are expected in other desert-adapted species.…”
Section: Effects Of Reproductive Arrest On Cold Tolerance and Energy mentioning
confidence: 99%
“…YUCCAs also promote drought resistance, and some FMOs are involved in osmoregulation in worms (85) and fish (88), in addition to producing the osmolyte TMAO in humans (43). Interestingly, there is overlap between the DR and osmotic stress pathways (89,90), and it is plausible that FMOs act at this intersection.…”
Section: Fmos and Aging In Non-mammalian Speciesmentioning
confidence: 99%